Evaluasi Pembinaan Ekstrakurikuler Pencak Silat di SMA Negeri 3 Slawi, SMA Negeri 1 Bojong, dan SMK Negeri 1 Bumijawa Kabupaten Tegal - Ramdani, Fawaz Syahrul; Setiawan, Ipang (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The coaching of pencak silat in schools plays an important role in both the development of sports achievement and the character building of students. Optimal coaching is influenced by school management, the quality of coaches, and the availability of adequate facilities and infrastructure. This study aims to evaluate the extracurricular pencak silat coaching system at SMA Negeri 3 Slawi, SMA Negeri 1 Bojong, and SMK Negeri 1 Bumijawa in Tegal Regency. The method used is descriptive qualitative, with data collection techniques including observation, in-depth interviews, and documentation. The research subjects consisted of coaches, student-athletes, and school management representatives. The results show that SMA Negeri 1 Bojong has a more structured and optimally functioning coaching system compared to the other two schools. This success is supported by certified coaches, proper facilities, and synergy between coaches, physical education teachers, and student affairs personnel. Meanwhile, the other two schools face challenges in program planning, training facilities, and budget support. This study recommends enhancing coach training and providing standardized facilities as strategies for improving coaching quality.